Parâmetros ecocardiográficos e variabilidade da frequência cardíaca em fêmeas caninas com sepse de ocorrência natural devido à piometra e suas correlações com valores séricos de TNF-alfa, IL-1 beta, IL-6, IL-10 e proteína C reativa - Pereira, Evandro Zacché [UNESP] (2015)
In order to assess myocardial and autonomic function in dogs with sepsis were studied 17 bitches diagnosed with pyometra and positive criteria for systemic inflammatory response syndrome. These animals underwent echocardiographic and heart rate variability tests, and also hematological evaluation, serum biochemistry, and serum TNF-α, IL-1β, IL-6, IL-10 and C-reactive protein, at diagnosis (T-0) and 15 (T-15) and 30 (T-30) days after hysterectomy. Among the echocardiographic parameters were observed decrease in E mitral flow deceleration time in T-0 relative to the T-30 (68.0 ± 49.1 and 111.0 ± 63.8; p = 0.035) and isovolumetric relaxation time in relation to T-0 and T-30 (61.5 ± 15.6 and 70.0 ± 13.6, p = 0.0002). It was also observed a significant negative correlation between indexes of systolic function, fractional shortening and ejection fraction, and the serum concentration of C-reactive protein (r = -0.324, p = 0.02 and r = -0.332, p = 0.01, respectively). Regarding the assessment of the autonomic system, there was a reduction of all parameters of heart rate variability in T-0 compared to other moments, with p <0.0001 for all indexes. Thus, under the circumstances of the present study, it was possible to conclude that female dogs with naturally occurring sepsis present autonomic dysfunction, reflected by the reduction of all parameters of heart rate variability, and C-reactive protein may play a pathogenic role in the progression of cardiac involvement